Pengaruh Pertumbuhan Penjualan dan Perputaran Total Asset Terhadap Profitabilitas - Rosmiati Tarmizi; Regina Kurniawati (Universitas Bandar Lampung (UBL), 2017)
This study is to identify the infuence of growth sales and total asset turnover on profitability in the otomotif and componen companies listed in Indonesia Stock Exchange period 2013-2015. The first hypothesis is growth sales positive influence on profitability and the second hypothesis is the total asset turnover that give positive influence on profitability. The sampel in this study is otomotif and componen companies listed in Indonesia Stock Exchange period 2013-2015 as 10 as much company. Analyze technique used in this study is multiple linier regression analyze. Hypothesis test is using t-test, and coefficient of determination. The classic assumption which consist of normality test, multicolinearity test, autocorrelation test and heteroskedasticity test had done in this study.The results showed that growth sales had positive and not significant influence on profitability and total asset turnover has positive in significant influence on profitabilitas in the otomotif dan componen companies listed on the Stock Exchange period 2013-2015.